Laparoscopic assistance for primary transanal pull-through in Hirschsprung's disease: a systematic review and meta-analysis. Issue 3 (24th March 2015) - Thomson, David; Allin, Benjamin; Long, Anna-May; Bradnock, Tim; Walker, Gregor; Knight, Marian
Abstract : Objective: To compare outcomes following totally transanal endorectal pull-through (TTERPT) versus pull-through with any form of laparoscopic assistance (LAPT) for infants with uncomplicated Hirschsprung's disease. Design: Systematic review and meta-analysis. Setting: Five hospitals with a paediatric surgical service. Participants: 405 infants with uncomplicated Hirschsprung's disease. Interventions: TTERPT versus LAPT. Primary and secondary outcome measures: Primary outcomes: mortality, postoperative enterocolitis, faecal incontinence, constipation, unplanned laparotomy or stoma formation, and injury to abdominal viscera. Secondary outcomes: Haemorrhage requiring transfusion of blood products, abscess formation, intestinal obstruction, intestinal ischaemia, enteric fistula formation, urinary incontinence or retention, impotency and duration of procedure. Results: Five eligible studies comprising 405 patients were identified from 2107 studies. All studies were retrospective case series, with variability in outcome assessment quality and length of follow-up. Operative duration was 50.29 min shorter with TTERPT (95% CI 39.83 to 60.74, p<0.00001). There were no significant differences identified between TTERPT and LAPT for incidence of postoperative enterocolitis (OR=0.78, 95% CI 0.44 to 1.38, p=0.39), faecal incontinence (OR=0.44, 95% CI 0.09 to 2.20, p=0.32) or constipation (OR=0.84, 95% CI 0.32 to 2.17, p=0.71). Conclusions: This meta-analysis did not find any evidence to suggest a higher rate of enterocolitis, incontinence or constipation following TTERPT compared with LAPT. Further long-term comparative studies and multicentre data pooling are needed to determine whether a purely transanal approach offers any advantages over a laparoscopically assisted approach to rectosigmoid Hirschsprung's disease. Trial registration number: PROSPERO registry- CRD42013005698.